Practicing harm reduction psychotherapy : an alternative approach to addictions - Denning, Patt, 1950-; Little, Jeannie (New York : Guilford Press, 2012)
'This acclaimed clinical guide has helped thousands of clinicians put the proven principles of harm reduction into practice with therapy clients who have substance use problems. Written by pioneers in the field, the book shows how to do effective therapeutic work with people still using alcohol or other drugs. It provides clear guidelines for conducting comprehensive assessments, making collaborative treatment decisions, and implementing interventions that combine motivational, cognitive-behavioral, and psychodynamic strategies. The focus is reducing drug-related harm while also addressing co-occurring psychological and emotional difficulties. Detailed clinical illustrations are featured throughout. New to This Edition *Reflects over a decade of research advances and the tremendous growth of harm reduction clinical practice and training. *Section on applications, with chapters on community-based settings, harm reduction groups, and working with families and friends. *Chapters on biological and psychodynamic aspects of treatment. *Expanded discussions of trauma, cultural sensitivity, and ethics. *Supplemental resources and training materials at the authors' website.'--Provided by publisher.
'Subject areas/key words: abstinence, addictions, addictive behaviors, alcoholism, counseling, dependence, drug abuse, dual diagnosis, harm reduction, interventions, psychotherapy, recovery, substance use disorders, treatments Brief Summary: This acclaimed clinical guide has helped thousands of clinicians put the proven principles of harm reduction into practice with therapy clients who have substance use problems. Written by pioneers in the field, the book shows how to do effective therapeutic work with people still using alcohol or other drugs. It provides clear guidelines for conducting comprehensive assessments, making collaborative treatment decisions, and implementing interventions that combine motivational, cognitive-behavioral, and psychodynamic strategies. The focus is reducing drug-related harm while also addressing co-occurring psychological and emotional difficulties. Detailed clinical illustrations are featured throughout'--Provided by publisher.
Machine generated contents note: I. Setting the Stage 1. Why Practice Harm Reduction Psychotherapy? 2. What Is Harm Reduction Psychotherapy and Who Is It For? II. Harm Reduction Psychotherapy as an Integrated Treatment 3. Assessment as Treatment 4. Developing a Treatment Plan 5. The Fundamentals of Harm Reduction Psychotherapy 6. The Psychodynamic Matrix of Harm Reduction Psychotherapy 7. Motivational and Cognitive-Behavioral Contributions to Harm Reduction Psychotherapy 8. The Role of Biology in Harm Reduction Psychotherapy III. Applications 9. Harm Reduction Psychotherapy in Community-Based Settings 10. Harm Reduction Psychotherapy in Groups 11. The Power of Connection: Working with Families and Friends of Drug Users 12. What Does It Take to Practice Harm Reduction Psychotherapy? Appendix A. Differential Diagnosis Appendix B. Harm Reduction Supervision, Edith Springer Appendix C. Additional Resources Appendix D. Recommended Readings.
Includes bibliographical references and indexes.
Keywords: Substance-Related Disorders -- prevention & control; Psychotherapy; Substance-Related Disorders -- therapy; Harm Reduction